2017
DOI: 10.1080/07420528.2017.1406493
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of chronotype for eating patterns in adolescents

Abstract: During adolescence, a shift from morningness to eveningness occurs, yet school continues to start early in the morning. Hence, adolescents are at risk for social jetlag, i.e. a discrepancy between biological and social timing. It remains to be determined whether chronotype associates with daily and daytime-specific eating patterns during this potentially critical period. Therefore, the aim of the present study was to investigate whether chronotype is decisive for daily eating patterns [total energy intake (TEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 45 publications
5
81
1
6
Order By: Relevance
“…The sole relevant study was conducted by Roßbach et al, which investigated the association between chronotype and skipping breakfast in a mixed sample of 223 individuals aged 10-18 in Germany [47]. Skipping breakfast was more often observed in children and adolescents with a later chronotype.…”
Section: Chronotype and Breakfast Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sole relevant study was conducted by Roßbach et al, which investigated the association between chronotype and skipping breakfast in a mixed sample of 223 individuals aged 10-18 in Germany [47]. Skipping breakfast was more often observed in children and adolescents with a later chronotype.…”
Section: Chronotype and Breakfast Consumptionmentioning
confidence: 99%
“…Individuals with different chronotypes were also found to have unique timing-related eating patterns [48,49]. The literature provides evidence for this assumption that the food intake behaviors of evening-type people shift towards later mealtimes in accordance with their later circadian preference compared with morning-type individuals [46,47,50]. However, the association between morning-type and skipping breakfast/having a small breakfast was no longer different in girls when total sleep time on school days was taken into account.…”
Section: Chronotype and Breakfast Consumptionmentioning
confidence: 99%
“…The present study also revealed an association between skipping meals and chronotype. Many previous studies have reported an association between skipping breakfast and evening type (27,44,45). Skipping breakfast is unhealthy eating behavior which contributes to metabolic disorders including obesity and diabetes (46,47).…”
Section: Discussionmentioning
confidence: 96%
“…Chronotype, the tendency towards morningness or eveningness underlying the circadian system, is in uenced by age, gender(1), genetics (24), and external environment/circumstances including light exposure (25) and sociocultural conditions (26). Late chronotype is often accompanied by unique eating behaviors (e.g., breakfast skipping, evening energy intake) (27,28), which result in metabolic disorders including obesity and diabetes (29,30). In addition, late chronotype is associated with poor mental health (31,32) and poor academic achievement in university students (33).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with sleep-wake cycle regulation, children who show increased evening caloric intake subsequently have little to no morning caloric intake. This dysregulation of meal timing in dark-light exposure has been shown to be positively correlated to an increase in weight gain, adiposity, and overall BMI scores in paediatric populations [20][21][22][23][24]. Many studies posit that perhaps these later feeding times could be a psychological result of chronotypes (nocturnal versus early bird tendencies): adolescents with evening chronotypes reportedly have phase delays in diurnal eating patterns, resulting in a higher prevalence of breakfast skipping and a shift in energy intake towards later in the day [24,25].…”
Section: Sleep Timing Feeding Times Caloric Intake and Weight Gainmentioning
confidence: 99%